Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Karyawan pada PT Sangwoo Indonesia - Kurniawati, Siti; Raharja, Irwan (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2025)
Leadership style and work discipline play an important role in improving employee performance. This research aims to examine the influence of leadership style and work discipline on employee performance at PT. Sangwoo Indonesia both partially and simultaneously. This research uses quantitative methods and data collection using questionnaires. Obtain population data on the total number of PT employees. Sangwoo Indonesia as many as 107 and a sample of 84 respondents using the Slovin formula. Data analysts use validity tests, reliability tests, classical assumption tests, hypothesis tests, namely the t test and f test, and partial and simultaneous coefficient of determination tests using SPSS 22. The results of this study show that the t test value on the leadership style variable t count > t table namely 1.794 > 1.663, while for the work discipline variable t count > t table, namely 13.914 > 1.663 so that each variable X has a partial effect on variable Y. Meanwhile, the f test produces a calculated f value > f table, namely 149.154 > 3.109 and a significant value of 0.000 > 0.05 so that Ha is accepted and Ho is rejected, meaning that leadership style and work discipline simultaneously have a significant and positive effect on employee performance. With the results of this research, it is hoped that the leadership of PT. Sangwoo Indonesia can continue to develop its leadership style as well as the employees of PT. Sangwoo Indonesia can continue to improve its work discipline to obtain maximum performance.